Pre-sleep casein ingestion with probiotic strains improves anaerobic power and lower-body-specific strength and power performance in soccer players - Reza Sadeghi; Mohammad Hemmatinafar; Fereshteh Eftekhari; Babak Imanian; Negar Koureshfard (Journal of the International Society of Sports Nutrition)
Background Probiotics comprise various strains that offer numerous health benefits. Researchers have recently focused on the relationship between probiotic consumption and improved gut microbiota function, enhanced digestion, increased nutrient absorption, and enhanced sports performance. Therefore, the present study investigated the effects of pre-sleep casein intake, coupled with probiotic strains, on soccer players’ anaerobic power, lower-body-specific strength, and power performance.Methods A randomized, double-blinded, and placebo-controlled study was conducted with forty-four male soccer players (Age: 22.81 ± 2.76 years, Height: 177.90 ± 6.75 cm, Weight: 67.42 ± 8.44 kg). The participants underwent the isokinetic strength, Wall-squat, and running-based anaerobic sprint (RAST) tests initially; then, they were randomly divided into four groups: probiotics (PRO), casein (CAS), probiotics with casein (PRO+CAS), and placebo (PLA). The PRO groups were given one probiotic capsule (containing eight bacterial strains: Lactiplantibacillus plantarum BP06, Lacticaseibacillus casei BP07, Lactobacillus acidophilus BA05, Lactobacillus bulgaricus BD08, Bifidobacterium infantis BI04, Bifidobacterium longum BL03, Bifidobacterium breve BB02, and Streptococcus thermophilus BT01, with a total dose of 4.5 × 1011 CFU) during dinner, while the CAS groups consumed 20 grams of casein powder 45 minutes before bed. The PRO+CAS group was given one probiotic capsule during dinner and 20 grams of casein powder 45 minutes before bed. The participants in the PLA group were given one red capsule (containing 5 grams of starch) during dinner. All participants were instructed to take the supplements only on training days, three times a week for four weeks. Additionally, isokinetic strength parameters, including absolute peak torque (APT) and average rate of force development (AvRFD), were measured for the knee extensors (ext) and flexors (flx) muscles (concentric phase at angular velocities of 60°/s and 180°/s, using the dominant leg). One-way analysis of covariance (ANCOVA) or Quade tests with a significance level of p < 0.05 was used to analyze the collected data.Result The current study’s findings indicated that APT-180°/s (ext) significantly increased in CAS (p = 0.008) and PRO+CAS (p = 0.003) compared to PLA. Additionally, the AvRFD-180°/s (ext) increased significantly in the PRO compared to the PLA (p = 0.007). Also, the AvRFD-60°/s (flx) increased significantly in the PRO+CAS group compared to the PLA (p = 0.014), CAS (p = 0.001), and PRO (p = 0.007). Furthermore, the AvRFD-180°/s (flx) increased significantly in the PRO+CAS compared to the CAS (p = 0.010). Moreover, the RAST average power increased dramatically in PRO+CAS compared to PLA (p = 0.003) and CAS (p = 0.02). Additionally, the Wall-squat test demonstrated a significant increase in PRO+CAS compared to PLA (p = 0.001) and PRO (p = 0.001). However, there were no significant differences in the APT-60°/s (ext&flx), APT-180°/s (flx), and AvRFD-60°/s (ext) between groups (p > 0.05).Conclusion The simultaneous consumption of casein and probiotics significantly improved anaerobic power, isokinetic strength, and lower-body muscular endurance in male soccer players. These enhancements were more pronounced than those observed with casein or probiotics alone, as supported by statistical significance and effect sizes. The findings suggest a synergistic benefit of combined supplementation for athletic performance.